Variable allelic expression of imprinted genes at the Peg13, Trappc9, Ago2 cluster in single neural cells - Claxton, Michael; Pulix, Michela; Seah, Michelle K. Y.; Bernardo, Ralph; Zhou, Peng; Aljuraysi, Sultan; Liloglou, Triantafillos; Arnaud, Philippe; Kelsey, Gavin; Messerschmidt, Daniel M.; Plagge, Antonius (Frontiers in Cell and Developmental Biology, 2022)
Genomic imprinting is an epigenetic process through which genes are expressed in a parent-of-origin specific manner resulting in mono-allelic or strongly biased expression of one allele. For some genes, imprinted expression may be tissue-specific and reliant on CTCF-influenced enhancer-promoter interactions. The Peg13 imprinting cluster is associated with neurodevelopmental disorders and comprises canonical imprinted genes, which are conserved between mouse and human, as well as brain-specific imprinted genes in mouse. The latter consist of Trappc9, Chrac1 and Ago2, which have a maternal allelic expression bias of ∼75% in brain. Findings of such allelic expression biases on the tissue level raise the question of how they are reflected in individual cells and whether there is variability and mosaicism in allelic expression between individual cells of the tissue. Here we show that Trappc9 and Ago2 are not imprinted in hippocampus-derived neural stem cells (neurospheres), while Peg13 retains its strong bias of paternal allele expression. Upon analysis of single neural stem cells and in vitro differentiated neurons, we find not uniform, but variable states of allelic expression, especially for Trappc9 and Ago2. These ranged from mono-allelic paternal to equal bi-allelic to mono-allelic maternal, including biased bi-allelic transcriptional states. Even Peg13 expression deviated from its expected paternal allele bias in a small number of cells. Although the cell populations consisted of a mosaic of cells with different allelic expression states, as a whole they reflected bulk tissue data. Furthermore, in an attempt to identify potential brain-specific regulatory elements across the Trappc9 locus, we demonstrate tissue-specific and general silencer activities, which might contribute to the regulation of its imprinted expression bias.